Correlation of nurses’ and midwives’ stress of conscience with hospital ethical climate and moral sensitivity - Magdalena Dziurka; Anna Jedynak; Krzysztof Jurek; Beata Dobrowolska (Scientific Reports)
Abstract Stress of conscience (SC) in healthcare professionals results from conflicts with ethical beliefs due to work constraints, while moral sensitivity (MS) and a positive ethical climate (EC) are crucial for ethical decision-making and quality patient care. The aim of the study was to assess correlation of the hospital EC, MS and SC among nurses, midwives; to assess psychometric properties of the Polish version of the Stress of Conscience Questionnaire (SCQ). An cross-sectional study was conducted from March 2019 to December 2020 among 683 nurses, midwives working at the hospital. The internal consistency reliability of the SCQ was satisfactory (0.837). A two-factor solution explained 54.26% of the total variance. The intensity of SC among the nurses, midwives increased with the deterioration of selected indicators of the EC of the hospital relationships with managers, the hospital, doctors; deterioration of relationships in these areas increased the subjects’ SC, while the overall indicator of the EC of the hospital remained independent of the intensity of SC. Respondents’ MS were higher the more EC of the hospital in which they worked was. Supporting a culture that values ethics and positive communication among healthcare professionals can create environments that enhance professional satisfaction and prioritize patient-oriented care.